Surrounded by setbacks ; or, how to succeed when everything's gone bad - Erikson, Thomas, 1965- (Vermilion, 2021)
Not everything goes the way we want it to - the world or people around us sometimes just spin out of control. Just consider the Covid pandemic for starters. Or how about that mad neighbour you have living next-door to you? Or when work seems to be going down the toilet when the competition keep outsmarting you? So how do you handle everything life throws your way when you'd really prefer to tell everyone to get stuffed? Thomas Erikson will help you turn adversity into success with the help of the behavioural model made famous in Surrounded by Idiots. Starting by reminding us that life is as it is, Erikson helps you see that it is in fact useless to try to control everything happening around you. Instead of protesting when life throws you curveballs, focus instead on how to handle them. Just as you keep the weeds away from the garden to provide space and amazing flowers, you need to find an approach to adversity that works for you and will give you the chance to turn everything into success. Surrounded by Setbacks will help you pinpoint the approach that works for you and will entertain and empower you in equal measure.